Nanocage‐Therapeutics Prevailing Phagocytosis and Immunogenic Cell Death Awakens Immunity against Cancer. Issue 10 (15th January 2018) - Lee, Eun Jung; Nam, Gi‐Hoon; Lee, Na Kyeong; Kih, Minwoo; Koh, Eunee; Kim, Yoon Kyoung; Hong, Yeonsun; Kim, Soyoun; Park, Seung‐Yoon; Jeong, Cherlhyun; Yang, Yoosoo; Kim, In‐San
Abstract: A growing appreciation of the relationship between the immune system and the tumorigenesis has led to the development of strategies aimed at "re‐editing" the immune system to kill tumors. Here, a novel tactic is reported for overcoming the activation‐energy threshold of the immunosuppressive tumor microenvironment and mediating the delivery and presentation of tumor neoantigens to the host's immune system. This nature‐derived nanocage not only efficiently presents ligands that enhance cancer cell phagocytosis, but also delivers drugs that induce immunogenic cancer cell death. The designed nanocage‐therapeutics induce the release of neoantigens and danger signals in dying tumor cells, and leads to enhancement of tumor cell phagocytosis and cross‐priming of tumor specific T cells by neoantigen peptide‐loaded antigen‐presenting cells. Potent inhibition of tumor growth and complete eradication of tumors is observed through systemic tumor‐specific T cell responses in tumor draining lymph nodes and the spleen and further, infiltration of CD8+ T cells into the tumor site. Remarkably, after removal of the primary tumor, all mice treated with this nanocage‐therapeutics are protected against subsequent challenge with the same tumor cells, suggesting development of lasting, tumor‐specific responses. This designed nanocage‐therapeutics "awakens" the host's immune system and provokes a durable systemic immune response against cancer. Abstract : Designed nanocage‐therapeutics induce the release of neoantigens and danger signals in dying cancer cells, enhance tumor cell phagocytosis, and cross‐prime tumor specific T cells by neoantigen peptide‐loaded antigen‐presenting cells (APCs). These nanocage‐therapeutics "awaken" the host's immune system to the presence of cancer and elicit a durable systemic immune response against cancer.